STUDI EVALUASI KEKUATAN STRUKTUR ATAP BETON DAK GEDUNG DPRD KABUPATEN POHUWATO - Saputra, Wawan Edi; Said, Sugira; Alia, Muh. Robin; Allo, Misel Boro (Universitas Bina Taruna Gorontalo, 2024)
This research was conducted to determine the damage or leakage of the concrete roof structure in the Pohuwato Regency DPRD Building based on the priority scale and investigation method. The location of the Pohuwato Regency People's Representative Council located in the Marisa Office Plan Block, Marisa District, Pohuwato Regency was used as the object of study in this study. This research survey was conducted in June. Several methods used were interviews with the DPRD Building Head Manager and interviews with the Head of the PU Service. This research was conducted in the Pohuwato Regency DPRD Building, with an emphasis on the concrete roof roof structure. The building is intended as one of the legislative institutions within the Pohuwato Regency Government. Based on the results and analysis, it can be concluded that the level of damage based on the weighting of the concrete roof roof of the Pohuwato Regency DPRD Building is 83%. This conclusion is based on the results of the analysis carried out by the author using the SAW method and the weighting parameters of the results, which indicate that the data can be used as a reference in analyzing or repairing the concrete roof roof of the Building.